Peran Guru Mata Pelajaran Matematika Dalam Mengatasi Kesulitan Belajar Siswa - Yakin Akbar Asikin; Ismawati Sibala; Nurhajjah Rasyid (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to determine the role of the mathematics teacher in overcoming the learning difficulties of sixth grade students at SD Islam Cokroaminoto 1, Kalabahi, Wetabua, Kec. Teluk Mutiara, Kab. Alor, Nusa Tenggara Timur. This study uses a qualitative approach. Data collection techniques through interviews, observation and documentation. Data analysis used descriptive analysis. The results of the study found that the difficulties experienced by students in mathematics subjects were students paying less attention to teacher explanations, students' lack of interest in mathematics, making mistakes when calculating especially in multiplication and division, low memory and concentration abilities, and different students' comprehension abilities. -different. The teacher's role in overcoming students' learning difficulties in mathematics subjects is that the teacher provides material and sample questions, as well as mentoring students and individual approaches to students, placing students who have difficulty in the front row, providing motivation to students, presenting interesting mathematical concepts and varied and create comfortable learning conditions and situation.